2020
DOI: 10.1111/idh.12428
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among dental hygienist and students of dental hygiene

Abstract: Objectives:The purpose of the present study was to present an up-to-date report on the prevalence of musculoskeletal complaints in dental hygienists and dental hygiene students in Israel. It examined the areas of the body that were most frequently affected and the intensity of pain in both groups. The possible differences between groups and the likelihood that musculoskeletal symptoms in students can be attributed to their workload. Method: A modified version of The Nordic Musculoskeletal Questionnaire (NMQ)wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…These results were consistent with the literature in regard to the most common sites for WRMSDs in healthcare and dental professionals 3,6,7,11,22 11 although other research has found higher prevalence of wrist and hand MSDs in dental hygienists ranging from 39 to 69% 8–10 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results were consistent with the literature in regard to the most common sites for WRMSDs in healthcare and dental professionals 3,6,7,11,22 11 although other research has found higher prevalence of wrist and hand MSDs in dental hygienists ranging from 39 to 69% 8–10 …”
Section: Discussionsupporting
confidence: 92%
“…However, a recent study with dentists and dental hygienists in Italy found the highest prevalence of WRMSDs 2–5 years after graduation 11 . In addition, other research has found MSDs in dental hygiene students suggesting it is common for WRMSDs to appear early on in the profession 8,23,24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are numerous studies on the prevalence of WMSD and ergonomic interventions [ 1 , 2 , 3 , 5 , 9 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], differentiations between the fields of specialization (e.g., general dentistry, endodontology, oral and maxillofacial surgery, or orthodontics) in these studies are rare [ 28 , 29 ]. Uppada et al [ 29 ], for example, found that oral surgeons show a higher prevalence of WMSD than generalists, while Newell and Kumar [ 28 ] argued for a different ergonomic load in orthodontists compared to generalists.…”
Section: Introductionmentioning
confidence: 99%